Berebut Bali: Pertarungan atas Ruang & Tata Kelola, by Agung Wardana, Yogyakarta: Insist Press, 2024, 364 pp., IDR 138,000 (paperback), ISBN 9786236179239 - Dhoni Zustiyantoro (Abjad Journal of Humanities & Education, 2025)
Bali, an enchanting island, has long been a magnet for visitors to Indonesia. With its rich natural and cultural heritage, the island has evoked an exotic imagination that has attracted global attention since the colonial era. However, the commercialisation of Bali has also given rise to complex spatial governance challenges, leading to prolonged social conflicts driven by the economic and political interests of entrepreneurs, politicians, and government officials. In his book, Berebut Bali: Pertarungan atas Ruang & Tata Kelola (Contesting Bali: The Struggle Over Space & Governance (2024), Agung Wardana presents a comprehensive analysis.